Non-supersymmetric non-tachyonic heterotic vacua with reduced rank in various dimensions - Carlo Angelantonj; Ioannis Florakis; Giorgio Leone; Diego Perugini (Journal of High Energy Physics)
Abstract We construct rigid non-supersymmetric heterotic vacua with reduced rank and no tachyons in six and four dimensions. These configurations are based on asymmetric orbifold compactifications which do not admit neutral deformation moduli and represent, to the best of our knowledge, the first instances of non-tachyonic non-supersymmetric heterotic vacua with reduced rank.